The role of Exenatide-GlP-1 receptor agonist- in the prevention and treatment of ovariectomy-induced osteoporosis in wistar rats - Sallat, Loujain Ghassan; Khattab, Marwan Abdo; Kasem, Mahmoud Kasem (Journal of natural sciences, life and applied sciences, 2022)
The present study aimed to investigate the protective and therapeutic effect of Exenatide on osteoporosis induced by ovariectomy in female Wister rats. The results of this study showed that administration of Exenatide at a dose of 10 mg/kg daily for 4 months led to a reduction in osteoporosis symptoms in ovariectomized rats, which was manifested by changes in serum levels of bone metabolism markers (a significant increase in the serum concentration of calcium, phosphorous, accompanied by a significant decrease in the potency of alkaline phosphatase), and a significant improvement in the tissue structure of the femur, in comparison with the members of the ovariectomized group. We conclude from this study the effectiveness of Exenatide in reducing the adverse effects of ovarian hormone deficiency on both bone structure and function in female Wister rats.